DAMPAK PENGGUNAAN WEBSITE JOBSTREET.CO.ID FRESH GRADUATE DI BANDAR LAMPUNG: DAMPAK PENGGUNAAN WEBSITE JOBSTREET.CO.ID FRESH GRADUATE DI BANDAR LAMPUNG - Ramadon, Mufti; Agung, Maulana; Septiani, Winda (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
The large number of graduates are not channeled into the fields or expertise that they already have, there are limitations in finding job vacancy information for fresh graduate students so that an application or system is needed that can recommend them in selecting job vacancies to be taken. This research aims to find out the degree of effectiveness of jobstreet websites as a job search portal to the information needs of fresh graduation students in Bandar Lampung. The variables used are website effectiveness (X) as independent variable and information needs (Y) as the dependent variable, this type of research is exploratory research with a quantitative approach to its research object is a fresh graduate student in Bandar Lampung. Data were collected using a questionnaire with a sample of 100 respondents. It is descriptively analyzed using the SPSS version 26 program. The partial test result between the jobstreet website effectiveness variable and the information needs variable was a significance value of 0 0.001 with a t-count of t t-table of 13,310 > 1,661 so that it could be interpreted that there was a positive and significant effect between jobstreet website effectiveness and information needs. The regression coefficient is 0.189 which means that every 1% increase in website effectiveness (X) will increase the information requirement (Y) will increase by 0.189. The effectiveness calculation results show that the jobstreet website is considered to be very effective in meeting the user's information needs with an effectiveness score of 87%.